DOI: 10.11606/d.11.2019.tde-20190821-122957
|View full text |Cite
|
Sign up to set email alerts
|

Nutrição mineral, crescimento e qualidade do óleo essencial da menta (>i<Mentha arvensis>/i< L.) cultivada em solução nutritiva

Abstract: Para determinação do efeito de nutrientes na qualidade do óleo essencial da Mentha arvensis, cultivou-se plantas submetidas a oito tratamentos em solução nutritiva completa, com omissão de nitrogênio, fósforo, potássio, cálcio, ferro, zinco e boro. O óleo essencial das folhas de cada tratamento foi extraído por destilação de arraste de vapor e analisado por cromatógrafo acoplado a espectrômetro de massa (GC-MS). A análise indicou sensíveis diferenças quanto ao número de componentes e à proporção de limoneno, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
12

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 2 publications
3
2
0
12
Order By: Relevance
“…The beneficial effects of increased nutrient availability for plant biomass production in this study were similar to those reported for several other species, including Mentha arvensis (7,9,11,18), Mentha piperita (10), Artemisia pallens (13), Anethum graveolens and Thymus vulgaris (23), Cymbopogon martini (14), Achillea millefolium (15), and Lippia alba (8). The lowest concentration of essential oils in our study was noted in plants grown with the highest level of nutrients, an observation previously reported for Anethum graveolens (23) and Lippia alba (8), but in direct contrast to results for Mentha arvensis (9,11) and Thymus vulgaris (23).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The beneficial effects of increased nutrient availability for plant biomass production in this study were similar to those reported for several other species, including Mentha arvensis (7,9,11,18), Mentha piperita (10), Artemisia pallens (13), Anethum graveolens and Thymus vulgaris (23), Cymbopogon martini (14), Achillea millefolium (15), and Lippia alba (8). The lowest concentration of essential oils in our study was noted in plants grown with the highest level of nutrients, an observation previously reported for Anethum graveolens (23) and Lippia alba (8), but in direct contrast to results for Mentha arvensis (9,11) and Thymus vulgaris (23).…”
Section: Discussionsupporting
confidence: 85%
“…Guenther (3) has indicated that precursors for production of essential oils could be obtained by carbohydrate and protein degradation. In addition, increases in oil yields similar to those observed in this study have been noted in such species as Artemisia pallens (13), Mentha piperita (10), Mentha arvensis (6,7,9,11,18), Thymus vulgaris (23), Cymbopogon martini (14), Achillea millefolium (15), and, with regard to root yield, Vetiveria zizanioides (1).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A lvl arvensís L. já foi definida há muito tempo como uma planta exigente quanto à nutrição (Finnemore, 1926;Guenther, 1949). A proporção entre as poucas raízes e a parte aérea da espécie foi apontado por Maia ( 1994) como um fator importante nessa característica da planta.…”
Section: Produtounclassified
“…Doses entre zero e 200 kg ha• 1 de N não chegaram a alterar o rendimento de óleo nos trabalhos de Singh & Singh (1989) (Kothari et al., 1987) Os poucos trabalhos encontrados sobre menta e K, mostram que o nutriente têm uma influência forte na absorção de N, taxa de respiração, e teor de óleo essencial (Sinha & Singh, 1984 ). Maia ( 1994) (Chiris, 1925: Brilho, 1969), que recomendavam a colheita no período de florescimento, para obter-se maiores rendimentos de mentol.…”
Section: Produtounclassified